Impact of storage conditions on the stability and biological efficacy of trans-arachidin-1 and trans-arachidin-3 - Ploy Khongrungjarat; Chonnikan Tothong; Chanyanut Pankaew; Suchada Phimsen; Nopawit Khamto; Nutthamon Kijchalao; Warissara Wongkham; Piyathida Wongkham; Wipaporn Chuaymaung; Adsadayu Thonnondang; Apinun Limmongkon (PLoS ONE, 2026)
Prenylated stilbenoids, particularly trans -arachidin-1 (Ara-1) and trans -arachidin-3 (Ara-3), have gained attention for their notable bioactivities and potential health-promoting properties. This study presents the first comprehensive investigation into the stability and biological efficacy of these compounds in both peanut hairy root culture crude extracts (PCE) and partially purified fractions derived from elicited peanut hairy root cultures. PCE stored at –20 °C and 4 °C maintained higher antioxidant capacity, total phenolic content compared to samples stored at room temperature. In cytotoxicity assays using SW480 colon cancer cells, the extract stored at –20 °C retained bioactivity with only minor changes in IC₅₀ values over three months, demonstrating superior stability under frozen conditions. Over a six-month period, partially purified fractions of Ara-1 and Ara-3 showed a time-dependent decline in compound content. However, Ara-3 maintained strong cytotoxicity against KKU-100 cholangiocarcinoma cells, while Ara-1 exhibited a significant loss in activity. These findings demonstrate that low-temperature storage, particularly at –20 °C, is crucial for preserving the chemical integrity and bioactivity of stilbenoid-rich extracts. The study underscores the importance of optimizing storage conditions to ensure consistent bioactivity, supporting the potential application of these compounds in the development of stable and effective pharmaceutical or nutraceutical products.